1995
DOI: 10.1007/bf02276719
|View full text |Cite
|
Sign up to set email alerts
|

Information processing in patients with early and continuously-treated phenylketonuria

Abstract: A bstract A total of 33 patients with early and continuously-treated phenylketonuria (PKU) between 7 and 16 years of age and 33 matched controls participated in a study ex amining perceptual, central, and re sponse-related mechanisms of infor mation processing. The specific mechanisms studied were: perceptual filtering, memory search, response selection, response execution, and motor presetting. In addition, groups were compared on mean intelligence level and task oriented behaviour. The performance of the PKU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 24 publications
0
31
0
7
Order By: Relevance
“…69 Notably, although studies have not been uniform, deficits in executive function in individuals with PAH deficiency are consistent enough to warrant special attention. 27,[72][73][74][75][76][77][78][79][80][81][82][83] …”
Section: Acmg Practice Guidelines Neurocognitive and Psychological Oumentioning
confidence: 99%
“…69 Notably, although studies have not been uniform, deficits in executive function in individuals with PAH deficiency are consistent enough to warrant special attention. 27,[72][73][74][75][76][77][78][79][80][81][82][83] …”
Section: Acmg Practice Guidelines Neurocognitive and Psychological Oumentioning
confidence: 99%
“…10 Early and continuous dietary therapy prevents the more severe neurological and intellectual dysfunction associated with classic PKU, but more subtle deficits in intelligence, academic achievement, and executive functioning can occur even in individuals with PKU who are treated early. [11][12][13] Despite functioning within the average range on tests of intelligence, children and adults with PKU have a lower mean intelligence quotient (IQ) than the general population. 12,14,15 Deficits affecting language skills, visual-spatial abilities, processing speed, verbal comprehension, and perceptual reasoning skills have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Despite functioning within the average range on tests of intelligence, children and adults with PKU have a lower mean intelligence quotient (IQ) than the general population. 12,14,15 Deficits affecting language skills, visual-spatial abilities, processing speed, verbal comprehension, and perceptual reasoning skills have also been reported. 13,[16][17][18][19][20] A meta-analysis of Phe levels and IQ in 40 studies confirmed a significant negative correlation between blood Phe levels and IQ in individuals with PKU who were treated early.…”
Section: Introductionmentioning
confidence: 99%
“…This includes even those that are not typically regarded as protein providers, such as fruits and vegetables. It is therefore common practice in Germany and many other, but not all, countries to calculate phe intake from all foods to achieve tolerable phe plasma concentrations (Burgard et al, 1999;Stemerdink et al, 2000;Anon, 2001).…”
Section: Introductionmentioning
confidence: 99%